Modified limestone powder and preparation method, 3D printed ultra-high performance concrete and preparation method

Through the modification of modified limestone powder and regenerative brick aggregate, the problem of insufficient mechanical properties in 3D printing concrete technology, high CO2 emissions and high cost of fine aggregate, and realized high -efficiency, environmentally friendly ultra -high performance concrete 3D printing technology.

CN116283009BActive Publication Date: 2025-01-28SOUTHEAST UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310327488.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-01-28
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The existing 3D printing concrete technology has problems such as insufficient mechanical properties, high CO2 emissions and high cost of fine aggregates.

Method used

By using modified limestone powder and modified regeneration brick aggregate, the modifiers such as hard fatty acid, laurel acid, and divergent latex are treated to improve the decentralization and filling effect of the particles, and reduce the aggregate effect. Water absorption rate.

Benefits of technology

Improve the mechanical properties and liquidity of concrete, reduce CO2 emissions and raw material costs, and realize the construction of 3D printing without high performance concrete and the construction of complex contour components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004153707710000121
    Figure BDA0004153707710000121
Patent Text Reader

Abstract

The present invention discloses a modified limestone powder and a preparation method, a 3D printed ultra-high performance concrete and a preparation method. The modified limestone powder comprises a limestone powder modifier, which comprises the following components in parts by mass: 2.5 to 10 parts of stearic acid, 1 to 4 parts of redispersible latex, 2 to 8 parts of lauric acid, 0.5 to 2 parts of toluene, and 19 to 76 parts of water. The concrete comprises modified limestone powder and modified recycled brick aggregate. The recycled brick aggregate modifier is composed of the following parts by mass: 2.5 to 10 parts of sodium silicate, 0.5 to 2 parts of propyltriethoxysilane, 0.5 to 2 parts of octyltriethoxysilane, and 21.5 to 86 parts of tap water. The modified limestone powder of the present invention improves the agglomeration phenomenon between particles, and the particles are evenly dispersed; the concrete of the present invention has excellent printability and high mechanical strength, and the 28d compressive strength can reach 130MPa, and the 28d flexural strength can reach 30MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to stone powder and a preparation method thereof, concrete and a preparation method thereof, and in particular to modified limestone powder and a preparation method thereof, and 3D printed ultra-high performance concrete and a preparation method thereof. Background Art

[0002] 3D printed concrete is a stable structure formed by stacking cement-based materials along a pre-set digital path. 3D printed concrete technology combines the intelligent features of computer tools to achieve optimal structural optimization, effectively reduce the use of building materials and thus reduce carbon emissions. In addition, no formwork is required during the construction process, which is very beneficial for the construction of complex structures or components, greatly improving the design freedom and effectively saving labor and resources.

[0003] The current 3D printing concrete technology has some limitations, making it difficult to add steel bars to 3D printed components, and often failing to meet the mechanical properties required for actual engineering. Combining ultra-high performance concrete (UHPC) with 3D printing can improve the mechanical strength of the structure from the source of the material while printing the structure without reinforcement and changing the brittle failure mode of plain concrete.

[0004] However, UHPC requires a large amount of cement (800-1000kg / m 3 ), which not only leads to a large amount of CO2 emissions, but also increases the risk of shrinkage cracking. And 3D printed concrete often requires a large amount of river sand as fine aggregate, which increases the cost of use. The hydration degree of cement in UHPC mixture is low (30-35%), and most of the cement and silica fume particles only have a filling effect. Therefore, abundant and easily available solid waste limestone powder can be used as an auxiliary cementitious material to prepare UHPC, which can fill voids, increase the system's bulk density, and reduce CO2 emissions; at the same time, using recycled brick aggregate to replace part of the fine aggregate can reduce the cost of raw materials.

[0005] However, limestone powder is prone to particle agglomeration after mechanical grinding, which not only has an adverse effect on the fluidity of the material, but also leads to insufficient filling effect due to uneven particle size distribution; recycled brick aggregates also have a porous surface and high water absorption, which will reduce the mechanical strength and fluidity when used to prepare concrete. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a modified limestone powder with good dispersibility;

[0007] The second object of the present invention is to provide a method for preparing the modified limestone powder;

[0008] The third object of the present invention is to provide a 3D printed ultra-high performance concrete with excellent mechanical properties;

[0009] A fourth object of the present invention is to provide a method for preparing the above-mentioned 3D printed ultra-high performance concrete.

[0010] Technical solution: The modified limestone powder of the present invention is prepared by compounding limestone powder and a limestone powder modifier; the limestone powder modifier comprises the following components in parts by weight: 2.5 to 10 parts of stearic acid, 1 to 4 parts of redispersible latex, 2 to 8 parts of lauric acid, 0.5 to 2 parts of toluene, and 19 to 76 parts of water.

[0011] The preparation method of the modified limestone powder comprises the following steps:

[0012] (1) mixing the components of the limestone powder modifier to obtain a modifier solution;

[0013] (2) slowly adding limestone powder to the modifier solution to obtain a modified limestone powder solution;

[0014] (3) sealing the modified limestone powder solution and placing it in a curing box for curing;

[0015] (4) The limestone powder in the cured modified limestone powder solution is separated from the solvent and vacuum dried to obtain the product.

[0016] Wherein, in step (1), the mixture is uniformly mixed at room temperature for 0.8 to 1.2 hours to obtain a modifier solution; in step (2), the mixture is uniformly stirred at a speed of 40 to 60 rpm for 8 to 12 minutes to obtain a modified limestone powder solution; in step (3), the mixture is cured in a 60±1° C. water tank for 20 to 28 hours; in step (4), the mixture is dried in a vacuum drying curing box at 60±1° C. for 20 to 28 hours.

[0017] The 3D printed ultra-high performance concrete of the present invention comprises the modified limestone powder and recycled brick aggregate.

[0018] The recycled brick aggregate is a modified recycled brick aggregate modified by a recycled brick aggregate modifier, and the recycled brick aggregate modifier comprises the following components in parts by mass: 2.5 to 10 parts of sodium silicate, 0.5 to 2 parts of propyltriethoxysilane, 0.5 to 2 parts of octyltriethoxysilane, and 21.5 to 86 parts of water.

[0019] Wherein, the modified recycled brick aggregate is prepared by the following steps:

[0020] (1) mixing the components of the recycled brick aggregate modifier to obtain a modifier solution;

[0021] (2) adding the recycled brick aggregate to the modifier solution to obtain a modified recycled brick aggregate solution;

[0022] (3) sealing the modified recycled brick aggregate solution and placing it in a curing box for curing;

[0023] (4) Separating the recycled brick aggregate from the solvent in the modified recycled brick aggregate solution and performing vacuum drying to obtain the modified recycled brick aggregate.

[0024] Wherein, in step (1), the mixture is uniformly mixed at room temperature for 0.8 to 1.2 hours to obtain a modifier solution; in step (2), the recycled brick aggregate is added to the mixed solution slowly and uniformly within 3 to 5 minutes; in step (3), the mixture is cured in a 20±1°C curing box for 28 to 36 hours; in step (4), the mixture is dried in a 60±1°C vacuum drying curing box for 20 to 28 hours.

[0025] The 3D printed ultra-high performance concrete comprises the following components in parts by mass:

[0026] 441-589.5 parts of cement,

[0027] 31.5-189 parts of limestone powder,

[0028] Silica fume 250-270 parts,

[0029] Limestone powder modifier 25-100 parts,

[0030] 55-330 parts of recycled brick aggregate,

[0031] 330-605 parts of coarse river sand,

[0032] 420-460 parts of fine river sand,

[0033] Recycled brick aggregate modifier 25-100 parts,

[0034] 142-162 parts of water,

[0035] 6.21-7.56 parts of polycarboxylate water reducer,

[0036] 120-140 parts of steel fiber.

[0037] The above-mentioned method for preparing 3D printed ultra-high performance concrete comprises the following steps:

[0038] (1) putting cement, silica fume, modified limestone powder, modified recycled brick aggregate, coarse river sand and fine river sand into a mixer and mixing to obtain a mixed dry material;

[0039] (2) mixing water and polycarboxylate water-reducing agent to prepare a mixed solution, adding a portion of the mixed solution to the mixed dry material, stirring, and obtaining a mixture;

[0040] (3) Pour the remaining part of the mixed solution into the mixture, add steel fiber during the stirring process, and stir evenly to obtain the mixture.

[0041] Wherein, in step (1), stirring is performed at a stirring speed of 40 to 60 rpm for 3 to 4 minutes to obtain a mixed dry material.

[0042] Wherein, in step (2), the volume of the mixed solution used accounts for 85-95% of the total volume of the mixed solution; the mixture is wet-mixed at a stirring speed of 40-60 rpm for 3-5 minutes until it is completely mixed.

[0043] In step (3), the remaining part of the mixed solution is poured into the mixture, and the mixture is stirred at a stirring speed of 40 to 60 rpm for 4 to 6 minutes, and during this process, the steel fibers are slowly and evenly added to the mixture through a sieve; then, the mixture is stirred at a stirring speed of 40 to 60 rpm for 3 to 5 minutes until the steel fibers are evenly dispersed.

[0044] Principle of the invention: Limestone powder reacts chemically with stearic acid, lauric acid, and redispersible latex components in the modifier. The redispersible latex powder forms an emulsion after contacting with water, and reacts on the surface of the limestone powder to form a highly flexible and highly adhesive hydrophobic film. Stearic acid and lauric acid will react with the water hydroxyl groups on the surface of the limestone powder to improve the dispersibility between the particle surfaces. Compared with ordinary solid waste limestone powder, the modified limestone powder improves the agglomeration phenomenon between particles, the particles are evenly dispersed, the fluidity and mechanical strength of the concrete are increased, and the internal pore structure is fully filled. The recycled brick aggregate undergoes a chemical reaction with the modifier, and the silane undergoes a dehydration reaction in an alkaline solution to form a Si-O-Si bond and a hydrophobic silicon film is formed on the surface of the recycled brick aggregate accompanied by the evaporation of water, thereby significantly reducing the water absorption rate of the recycled aggregate and improving the fluidity and extrudability of 3D printed concrete. At the same time, sodium silicate solution has good bonding, penetration and filling effects, forming a layer of crystal inclusions on the surface of recycled aggregate, filling pores and microcracks, and increasing the strength of recycled aggregate.

[0045] Beneficial effects: Compared with the prior art, the present invention has achieved the following significant effects: (1) Compared with ordinary solid waste limestone powder, the modified limestone powder of the present invention improves the agglomeration phenomenon between particles, and the particles are evenly dispersed; (2) The present invention adopts the classic Anderson powder particle accumulation model for calculation, realizes the gradation adjustment of the material, and uses the filling effect of the modified limestone powder to fill the pores, reducing the porosity by about 10%, thereby further improving the mechanical properties of the concrete; (3) The modified limestone powder and modified recycled brick aggregate are used at the same time, making the mechanical properties of the concrete more excellent; (4) The ultra-high performance concrete material is introduced into the 3D printed concrete, and its extremely high bending and compressive strength and toughness are used to change the brittle failure mode of the original 3D printed plain concrete; the concrete material of the present invention can reach a 28d compressive strength of 130MPa, and a 28d flexural strength of 30MPa. The material provides a solution for realizing the unreinforced construction of concrete structures and the construction of complex contour components. (5) Modified limestone powder and recycled brick aggregate, which are easily available, are used to replace part of the cement and fine aggregate, respectively, which significantly reduces the production energy consumption and economic cost of raw materials; the material conforms to the concept of green production, improves environmental benefits, and promotes the sustainable development of new building materials. (6) The present invention proposes a comprehensive evaluation method for 3D printing ultra-high performance concrete materials. Through printability tests, mechanical properties tests and CO2 emission calculations, it is judged whether the material can be 3D printed, whether the mechanical properties meet the requirements, and whether it is low-carbon and environmentally friendly. The application value and feasibility of developing the material are evaluated from the two starting points of performance and environmental benefits. DETAILED DESCRIPTION

[0046] The present invention is described in further detail below.

[0047] Example 1

[0048] The present embodiment provides a 3D printed ultra-high performance concrete, which uses a limestone powder modifier and a recycled brick aggregate modifier. The above-mentioned limestone powder modifier is composed of the following components in parts by mass: 2.5 parts of stearic acid, 1 part of redispersible latex, 2 parts of lauric acid, 0.5 parts of toluene, and 19 parts of tap water; the above-mentioned recycled brick aggregate modifier is composed of the following components in parts by mass: 2.5 parts of sodium silicate, 0.5 parts of propyltriethoxysilane, 0.5 parts of octyltriethoxysilane, and 21.5 parts of tap water.

[0049] The preparation and use of the above-mentioned stone powder modifier are as follows:

[0050] (1) uniformly mixing the components of the limestone powder modifier at room temperature for 0.8 h to obtain a modifier solution;

[0051] (2) adding the limestone powder to the modifier solution slowly and uniformly, and stirring uniformly at a speed of 40 rpm for 8 min to obtain a modified limestone powder solution;

[0052] (3) The modified limestone powder solution is sealed and placed in a 60°C water tank for curing for 20 hours;

[0053] (4) The modified limestone powder solution is separated from the solvent by a suction filtration device, and placed in a vacuum drying and curing oven at 60° C. for 20 hours to obtain the final modified limestone powder.

[0054] The preparation and use methods of the above-mentioned recycled brick aggregate modifier are as follows:

[0055] (1) uniformly mixing the components of the recycled brick powder modifier at room temperature for 0.8 h to obtain a modifier solution;

[0056] (2) adding all the recycled brick aggregates to the modifier solution at a uniform speed and slowly over 3 minutes to obtain a modified recycled brick aggregate solution;

[0057] (3) The modified recycled brick aggregate solution is sealed and placed in a 20°C curing box for 28 hours;

[0058] (4) The recycled brick aggregate in the modified recycled brick aggregate is separated from the solvent by a filtering device, and placed in a vacuum drying and curing box at 60° C. for 20 hours to obtain the final modified recycled brick aggregate.

[0059] The above-mentioned 3D printed ultra-high performance concrete is composed of the following components in parts by mass: 589.5 parts of PⅡ52.5r type cement, 31.5 parts of limestone powder, 250 parts of silica fume, 25 parts of limestone powder modifier, 55 parts of recycled brick aggregate, 605 parts of coarse river sand, 420 parts of fine quartz sand, 25 parts of recycled brick aggregate modifier, 162 parts of tap water, 7.56 parts of polycarboxylic acid water reducer, and 120 parts of steel fiber.

[0060] The preparation method of the above 3D printed ultra-high performance concrete material comprises the following steps:

[0061] (1) Put cement, silica fume, modified limestone powder, modified recycled brick aggregate, coarse river sand and fine river sand into a mixer and mix them at a stirring speed of 40 rpm for 3 minutes to obtain a mixed dry material;

[0062] (2) Mix tap water and polycarboxylate water reducer to prepare a mixed solution, add 90% of the mixed solution to the mixed dry material, and wet mix at a stirring speed of 40 rpm for 3 minutes until the mixture is completely mixed to obtain a mixture;

[0063] (3) Pour the remaining 10% of the mixed solution into the mixture, stir at a stirring speed of 40 rpm for 4 min, and during this process, slowly and evenly add the steel fiber into the mixture through a sieve;

[0064] (4) The mixture obtained in step (3) was stirred at a stirring speed of 40 rpm for 3 min until the steel fibers were uniformly dispersed, thereby obtaining a product.

[0065] The above-mentioned 3D printed ultra-high performance concrete material performance evaluation method is characterized in that the 3D printed ultra-high performance concrete must meet the following technical requirements:

[0066] (1) The fluidity of 3D printed ultra-high performance concrete needs to be between 155 mm and 185 mm;

[0067] (2) The cumulative printing height of the 3D printed ultra-high performance concrete components exceeds 90% of the component design height and the printed strips are extruded smoothly;

[0068] (3) The 28d compressive strength of 3D printed concrete is greater than 100MPa and the 28d flexural strength is greater than 12MPa.

[0069] The environmental benefit evaluation method of the above-mentioned 3D printed ultra-high performance concrete material is as follows: the CO2 emissions of the prepared 3D printed ultra-high performance concrete are calculated, and the environmental benefits and sustainability of the material are evaluated in kg / ton.

[0070] The applications of the above-mentioned 3D printed ultra-high performance concrete materials include architectural 3D printing, unreinforced construction of concrete structures, or construction of complex contour components.

[0071] The fluidity of the above-mentioned 3D printed ultra-high performance concrete material is 155mm, which is relatively low. After the printing test, the extruded concrete strips have a uniform width and no discontinuity, and have good extrudability. Under the design height of the component of 200mm, the actual printing height is 197mm, and the constructability is excellent.

[0072] In the application of architectural 3D printing, the basic mechanical properties of the printed structure of the above-mentioned 3D printed ultra-high performance concrete material include: compressive strength index of 132.1MPa, flexural strength index of 31.5MPa, and the specimen showed strain hardening phenomenon under flexural loading, with excellent mechanical properties.

[0073] The calculated CO2 emissions of the above 3D printed ultra-high performance concrete material is 241.91 kg / ton.

[0074] Example 2

[0075] The present embodiment provides a 3D printed ultra-high performance concrete, which uses a limestone powder modifier and a recycled brick aggregate modifier. The above-mentioned limestone powder modifier is composed of the following components in parts by mass: 5 parts of stearic acid, 2 parts of redispersible latex, 4 parts of lauric acid, 1 part of toluene, and 38 parts of tap water; the above-mentioned recycled brick aggregate modifier is composed of the following components in parts by mass: 5 parts of sodium silicate, 1 part of propyltriethoxysilane, 1 part of octyltriethoxysilane, and 43 parts of tap water.

[0076] The preparation and use of the above-mentioned limestone powder modifier are as follows:

[0077] (1) uniformly mixing the components of the modifier at room temperature for 1 hour to obtain a modifier solution;

[0078] (2) adding the limestone powder to the modifier solution slowly and uniformly, and stirring uniformly at a speed of 45 rpm for 10 min to obtain a modified limestone powder solution;

[0079] (3) The modified limestone powder solution is sealed and placed in a 60°C water tank for curing for 24 hours;

[0080] (4) The modified limestone powder solution is separated from the solvent by a suction filtration device, and placed in a vacuum drying and curing oven at 60° C. for 24 hours to obtain the final modified limestone powder.

[0081] The preparation and use methods of the above-mentioned recycled brick aggregate modifier are as follows:

[0082] (1) uniformly mixing the components of the recycled brick powder modifier at room temperature for 1 hour to obtain a modifier solution;

[0083] (2) adding all the recycled brick aggregates to the modifier solution at a uniform speed and slowly over 4 minutes to obtain a modified recycled brick aggregate solution;

[0084] (3) The modified recycled brick aggregate solution is sealed and placed in a 20°C curing box for 32 hours;

[0085] (4) The recycled brick aggregate in the modified recycled brick aggregate solution is separated from the solvent by a filtering device, and the solution is placed in a vacuum drying and curing box at 60° C. for 24 hours to obtain the final modified recycled brick aggregate.

[0086] The above-mentioned 3D printed ultra-high performance concrete is composed of the following components in parts by mass: 558 parts of PⅡ52.5r type cement, 63 parts of limestone powder, 255 parts of silica fume, 50 parts of limestone powder modifier, 110 parts of recycled brick aggregate, 550 parts of coarse river sand, 430 parts of fine river sand, 50 parts of recycled brick aggregate modifier, 157 parts of tap water, 7.30 parts of polycarboxylic acid water reducer, and 125 parts of steel fiber.

[0087] The preparation method of the above 3D printed ultra-high performance concrete material comprises the following steps:

[0088] (1) Put cement, silica fume, modified limestone powder, modified recycled brick aggregate, and river sand into a mixer and mix them at a stirring speed of 45 rpm for 4 minutes to obtain a mixed dry material;

[0089] (2) Mix tap water and polycarboxylate water reducer to prepare a mixed solution, add 90% of the mixed solution to the dry material, and wet mix at a stirring speed of 45 rpm for 4 minutes until the mixture is completely mixed to obtain a mixture;

[0090] (3) Pour the remaining 10% of the mixed solution into the mixture and stir it at a stirring speed of 45 rpm for 5 min. During this process, slowly and evenly add the steel fiber into the mixture through the sieve;

[0091] (4) The mixture obtained in step (3) was stirred at a stirring speed of 45 rpm for 4 min until the steel fibers were uniformly dispersed, thereby obtaining a product.

[0092] The above-mentioned 3D printed ultra-high performance concrete material performance evaluation method is characterized in that the 3D printed ultra-high performance concrete must meet the following technical requirements:

[0093] (1) The fluidity of 3D printed ultra-high performance concrete needs to be between 155 mm and 185 mm;

[0094] (2) The cumulative printing height of the 3D printed ultra-high performance concrete components exceeds 90% of the component design height and the printed strips are extruded smoothly;

[0095] (3) The 28d compressive strength of 3D printed concrete is greater than 100MPa and the 28d flexural strength is greater than 12MPa.

[0096] The environmental benefit evaluation method of the above-mentioned 3D printed ultra-high performance concrete material is as follows: the environmental benefit and sustainability of the material are evaluated by calculating the CO2 emissions (kg / ton) of the prepared 3D printed ultra-high performance concrete.

[0097] The applications of the above-mentioned 3D printed ultra-high performance concrete materials include architectural 3D printing, unreinforced construction of concrete structures, or construction of complex contour components.

[0098] The above-mentioned 3D printed ultra-high performance concrete material has a fluidity of 167mm, which has moderate fluidity and is suitable for printing. After the printing test, the extruded concrete strips are uniform, continuous and uninterrupted, and under the component design height of 200mm, the actual printing height is 197mm, with excellent printability.

[0099] In the application of architectural 3D printing, the basic mechanical properties of the printed structure of the above-mentioned 3D printed ultra-high performance concrete material include: compressive strength index of 138.2MPa, flexural strength index of 32.97MPa, and the specimen showed strain hardening phenomenon when subjected to flexural loading, with excellent mechanical properties.

[0100] The calculated CO2 emissions of the above 3D printed ultra-high performance concrete material is 229.59kg / ton.

[0101] Example 3

[0102] The present embodiment provides a 3D printed ultra-high performance concrete, which uses a limestone powder modifier and a recycled brick aggregate modifier. The above-mentioned limestone powder modifier is composed of the following components in parts by mass: 7.5 parts of stearic acid, 3 parts of redispersible latex, 6 parts of lauric acid, 1.5 parts of toluene, and 57 parts of tap water; the above-mentioned recycled brick aggregate modifier is composed of the following components in parts by mass: 7.5 parts of sodium silicate, 1.5 parts of propyltriethoxysilane, 1.5 parts of octyltriethoxysilane, and 64.5 parts of tap water.

[0103] The preparation and use of the above-mentioned limestone powder modifier are as follows:

[0104] (1) uniformly mixing the components of the modifier at room temperature for 1.1 h to obtain a modifier solution;

[0105] (2) adding the limestone powder to the modifier solution slowly and uniformly, and stirring uniformly at a speed of 55 rpm for 10 min to obtain a modified limestone powder solution;

[0106] (3) The modified limestone powder solution is sealed and placed in a 60°C water tank for curing for 26 hours;

[0107] (4) The modified limestone powder solution is separated from the solvent by a suction filtration device, and placed in a vacuum drying and curing oven at 60° C. for 26 hours to obtain the final modified limestone powder.

[0108] The preparation and use methods of the above-mentioned recycled brick aggregate modifier are as follows:

[0109] (1) uniformly mixing the components of the recycled brick powder modifier at room temperature for 1.1 h to obtain a modifier solution;

[0110] (2) adding all the recycled brick aggregates to the modifier solution at a uniform speed and slowly over a period of 4.5 minutes to obtain a modified recycled brick aggregate solution;

[0111] (3) The modified recycled brick aggregate solution is sealed and placed in a 20°C curing box for 34 hours;

[0112] (4) The recycled brick aggregate in the modified recycled brick aggregate is separated from the solution by a filtering device, and placed in a vacuum drying and curing box at 60° C. for 26 hours to obtain the final modified recycled brick aggregate.

[0113] The above-mentioned 3D printed ultra-high performance concrete is composed of the following components in parts by mass: 495 parts of PⅡ52.5r type cement, 126 parts of limestone powder, 260 parts of silica fume, 75 parts of limestone powder modifier, 220 parts of recycled brick aggregate, 440 parts of coarse river sand, 440 parts of fine river sand, 75 parts of recycled brick aggregate modifier, 148 parts of tap water, 6.93 parts of polycarboxylic acid water reducer, and 135 parts of steel fiber.

[0114] The preparation method of the above 3D printed ultra-high performance concrete material comprises the following steps:

[0115] (1) Put cement, silica fume, modified limestone powder, modified recycled brick aggregate, and river sand into a mixer and mix them at a stirring speed of 55 rpm for 3.5 min to obtain a mixed dry material;

[0116] (2) Mix tap water and polycarboxylate water reducer to prepare a mixed solution, add 90% of the mixed solution to the mixed dry material, and wet mix at a stirring speed of 55 rpm for 4.5 min until the mixture is completely mixed to obtain a mixture;

[0117] (3) Pour the remaining 10% of the mixed solution into the mixture and stir it at a stirring speed of 55 rpm for 5.5 min. During this process, slowly and evenly add the steel fiber into the mixture through the sieve;

[0118] (4) The mixture obtained in step (3) was stirred at a stirring speed of 55 rpm for 4.5 min until the steel fibers were uniformly dispersed, thereby obtaining a product.

[0119] The above-mentioned 3D printed ultra-high performance concrete material performance evaluation method is characterized in that the 3D printed ultra-high performance concrete must meet the following technical requirements:

[0120] (1) The fluidity of 3D printed ultra-high performance concrete needs to be between 155 mm and 185 mm;

[0121] (2) The cumulative printing height of the 3D printed ultra-high performance concrete components exceeds 90% of the component design height and the printed strips are extruded smoothly;

[0122] (3) The 28d compressive strength of 3D printed concrete is greater than 100MPa and the 28d flexural strength is greater than 12MPa.

[0123] The environmental benefit evaluation method of the above-mentioned 3D printed ultra-high performance concrete material is as follows: the environmental benefit and sustainability of the material are evaluated by calculating the CO2 emissions (kg / ton) of the prepared 3D printed ultra-high performance concrete.

[0124] The applications of the above-mentioned 3D printed ultra-high performance concrete materials include architectural 3D printing, unreinforced construction of concrete structures, or construction of complex contour components.

[0125] The above-mentioned 3D printed ultra-high performance concrete material has a fluidity of 170mm, which has moderate fluidity and is suitable for printing. After the printing test, the extruded concrete strips are uniform, continuous and uninterrupted, and under the component design height of 200mm, the actual printing height is 195mm, with excellent printability.

[0126] In the application of architectural 3D printing, the basic mechanical properties of the printed structure of the above-mentioned 3D printed ultra-high performance concrete material include: compressive strength index of 125.17MPa, flexural strength index of 28.12MPa, and the specimen showed strain hardening phenomenon when subjected to flexural loading, with excellent mechanical properties.

[0127] The calculated CO2 emissions of the above 3D printed ultra-high performance concrete material is 204.97kg / ton.

[0128] Example 4

[0129] The present embodiment provides a 3D printed ultra-high performance concrete, which uses a limestone powder modifier and a recycled brick aggregate modifier. The limestone powder modifier is composed of the following components in parts by mass: 10 parts of stearic acid, 4 parts of redispersible latex, 8 parts of lauric acid, 2 parts of toluene, and 76 parts of tap water; the recycled brick aggregate modifier is composed of the following components in parts by mass: 10 parts of sodium silicate, 2 parts of propyltriethoxysilane, 2 parts of octyltriethoxysilane, and 86 parts of tap water;

[0130] The preparation and use of the above-mentioned limestone powder modifier are as follows:

[0131] (1) The components of the limestone powder modifier are uniformly mixed at room temperature for 1.2 hours to obtain a modifier solution;

[0132] (2) adding the limestone powder to the modifier solution slowly and uniformly, and stirring uniformly at a speed of 60 rpm for 12 min to obtain a modified limestone powder solution;

[0133] (3) The modified limestone powder solution is sealed and placed in a 60°C water tank for curing for 28 hours;

[0134] (4) The modified limestone powder solution is separated from the solvent by a suction filtration device, and placed in a vacuum drying and curing oven at 60° C. for 28 hours to obtain the final modified limestone powder.

[0135] The preparation and use of the above-mentioned modifier for recycled brick aggregate are as follows:

[0136] (1) uniformly mixing the components of the recycled brick powder modifier at room temperature for 1.2 hours to obtain a modifier solution;

[0137] (2) adding all the recycled brick aggregates to the modifier solution at a uniform speed and slowly over 5 minutes to obtain a modified recycled brick aggregate solution;

[0138] (3) The modified recycled brick aggregate solution is sealed and placed in a 20°C curing box for 36 hours;

[0139] (4) The recycled brick aggregate in the modified recycled brick aggregate solution is separated from the solvent by a filtering device, and the solution is placed in a vacuum drying and curing box at 60° C. for 28 hours to obtain the final modified recycled brick aggregate.

[0140] The above-mentioned 3D printed ultra-high performance concrete is composed of the following components in parts by mass: 441 parts of PⅡ52.5r type cement, 189 parts of limestone powder, 270 parts of silica fume, 100 parts of limestone powder modifier, 330 parts of recycled brick aggregate, 330 parts of coarse river sand, 460 parts of fine river sand, 142 parts of tap water, 6.21 parts of polycarboxylic acid water reducer, and 140 parts of steel fiber.

[0141] The preparation method of the above 3D printed ultra-high performance concrete material is as follows:

[0142] (1) Put cement, silica fume, modified limestone powder, modified recycled brick aggregate, and river sand into a mixer and mix them at a stirring speed of 60 rpm for 4 minutes to obtain a mixed dry material;

[0143] (2) Mix tap water and polycarboxylate water reducer to prepare a mixed solution, add 90% of the mixed solution to the dry material, and wet mix at a stirring speed of 60 rpm for 5 minutes until the mixture is completely mixed to obtain a mixture;

[0144] (3) Pour the remaining 10% of the mixed solution into the mixture and stir it at a stirring speed of 60 rpm for 6 min. During this process, slowly and evenly add the steel fiber into the mixture through the sieve;

[0145] (4) The mixture obtained in step (3) was stirred at a stirring speed of 60 rpm for 5 min until the steel fibers were evenly dispersed, thereby obtaining a product.

[0146] The above-mentioned 3D printed ultra-high performance concrete material performance evaluation method is characterized in that the 3D printed ultra-high performance concrete must meet the following technical requirements:

[0147] (1) The fluidity of 3D printed ultra-high performance concrete needs to be between 155 mm and 185 mm;

[0148] (2) The cumulative printing height of the 3D printed ultra-high performance concrete components exceeds 90% of the component design height and the printed strips are extruded smoothly;

[0149] (3) The 28d compressive strength of 3D printed concrete is greater than 100MPa and the 28d flexural strength is greater than 12MPa.

[0150] The environmental benefit evaluation method of the above-mentioned 3D printed ultra-high performance concrete material is as follows: the environmental benefit and sustainability of the material are evaluated by calculating the CO2 emissions of the prepared 3D printed ultra-high performance concrete.

[0151] The applications of the above-mentioned 3D printed ultra-high performance concrete materials include architectural 3D printing, unreinforced construction of concrete structures, or construction of complex contour components.

[0152] The above 3D printed ultra-high performance concrete material has a fluidity of 185mm, which is relatively fluid. After the printing test, the extruded concrete strips are uniform, continuous and uninterrupted, but under the design height of the component of 200mm, the actual printing height is 183mm, which shows a certain collapse. Therefore, the material has excellent extrudability but insufficient constructability.

[0153] In the application of architectural 3D printing, the basic mechanical properties of the printed structure of the above-mentioned 3D printed ultra-high performance concrete material include: compressive strength index of 109.2MPa, flexural strength index of 20.7MPa, no strain hardening phenomenon of the specimen during flexural loading, and relatively excellent mechanical properties.

[0154] The calculated CO2 emissions of the above 3D printed ultra-high performance concrete material is 179.99kg / ton.

[0155] Comparative Example 1

[0156] On the basis of Example 3, the difference from Example 3 is that the modified limestone powder is replaced by ordinary limestone powder.

[0157] Comparative Example 2

[0158] On the basis of Example 3, the difference from Example 3 is that the modified recycled brick aggregate is replaced by ordinary recycled brick aggregate.

[0159] Comparative Example 3

[0160] On the basis of Example 3, the difference from Example 3 is that the mass fraction of stearic acid in the limestone powder modifier is set to 0.

[0161] Comparative Example 4

[0162] On the basis of Example 3, the difference from Example 3 is that the mass fraction of the redispersible latex in the limestone powder modifier is set to 0.

[0163] Comparative Example 5

[0164] On the basis of Example 3, the difference from Example 3 is that the mass fraction of lauric acid in the limestone powder modifier is set to 0.

[0165] Comparative Example 6

[0166] On the basis of Example 3, the difference from Example 3 is that the mass fraction of sodium silicate in the recycled brick aggregate modifier is set to 0.

[0167] Comparative Example 7

[0168] On the basis of Example 3, the difference from Example 3 is that the mass fraction of propyltriethoxysilane in the recycled brick aggregate modifier is set to 0.

[0169] Comparative Example 8

[0170] On the basis of Example 3, the difference from Example 3 is that the mass fraction of octyltriethoxysilane in the recycled brick aggregate modifier is set to 0.

[0171] The various performance and environmental benefit evaluation indicators of the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 8 are shown in Table 1.

[0172] Table 1

[0173]

[0174] As can be seen from Table 1, in general, the extrudability of Examples 1 to 4 is very excellent, the strips are uniform, continuous and uninterrupted, the greater the amount of modified limestone powder and modified recycled brick aggregate composite replacing cement and fine aggregate, the greater the fluidity, and the more conducive to the extrusion of the strips; Examples 1 to 3 have no obvious collapse phenomenon during the component printing process, and have excellent constructability, while Example 4 has a certain collapse of the printed component due to the large fluidity of the material, but the collapse height <10% is still within an acceptable range. And the mechanical properties of Examples 1 to 4 are relatively excellent, meeting the mechanical properties requirements of the national standard "Active Powder Concrete" (GB / T31387-2015) for ultra-high performance concrete, and Examples 1 and 2 illustrate that adding a small amount of modified limestone powder and modified recycled brick aggregate can improve the compressive and flexural strength of the printed component to a certain extent; Examples 1 to 4 illustrate that the greater the amount of modified limestone powder and modified recycled brick aggregate added, the lower the CO2 emission per unit mass of raw materials.

[0175] The experimental results of comparative examples 1 to 2 show that limestone powder and recycled brick aggregates must undergo certain modification treatments, otherwise the printability is poor and the mechanical strength of the printed specimens is low. The experimental results of comparative examples 3 to 5 show that the stearic acid component has the best modification effect on limestone powder, but the lack of any of the three modified components will have an adverse effect on the rheological properties and mechanical properties of 3D printed ultra-high performance concrete materials. The experimental results of comparative examples 6 to 8 show that sodium silicate is the most critical component in the recycled brick aggregate modifier, which is also because sodium silicate not only provides an alkaline environment for silane, but also has good bonding, penetration and filling effects. Propyl triethoxysilane has a better modification effect on improving the strength of recycled brick aggregates, while octyl triethoxysilane has a better modification effect on reducing the water absorption of recycled brick aggregates and improving the fluidity of concrete. Under the composite action of the internal components of the limestone powder modifier and the recycled brick aggregate modifier, the maximum modification effect can be exerted, so that the prepared 3D print exceeds the high-performance concrete and achieves the excellent performance shown in Example 3.

Claims

1. A 3D printed ultra-high performance concrete, characterized in that: Contains modified limestone powder and recycled brick aggregate; The modified limestone powder is prepared by compounding limestone powder with a limestone powder modifier; the limestone powder modifier comprises the following components in parts by weight: 2.5 to 10 parts of stearic acid, 1 to 4 parts of redispersible latex, 2 to 8 parts of lauric acid, 0.5 to 2 parts of toluene, and 19 to 76 parts of water; The recycled brick aggregate is a modified recycled brick aggregate modified by a recycled brick aggregate modifier, and the recycled brick aggregate modifier comprises the following components in parts by mass: 2.5 to 10 parts of sodium silicate, 0.5 to 2 parts of propyltriethoxysilane, 0.5 to 2 parts of octyltriethoxysilane, and 21.5 to 86 parts of water; The 3D printed ultra-high performance concrete comprises the following components by weight: 441-589.5 parts of cement, 31.5-189 parts of limestone powder, Silica fume 250-270 parts, Limestone powder modifier 25-100 parts, 55-330 parts of recycled brick aggregate, 330-605 parts of coarse river sand, 420-460 parts of fine river sand, Recycled brick aggregate modifier 25-100 parts, 142-162 parts of water, 6.21-7.56 parts of polycarboxylate water reducer, 120-140 parts of steel fiber.

2. The 3D printed ultra-high performance concrete according to claim 1, characterized in that: The preparation method of the modified limestone powder comprises the following steps: (1) Mixing the components of the limestone powder modifier to obtain a modifier solution; (2) slowly adding limestone powder to the modifier solution to obtain a modified limestone powder solution; (3) Seal the modified limestone powder solution and place it in a curing box for curing; (4) The limestone powder and the solvent in the cured modified limestone powder solution are separated and vacuum dried to obtain the product.

3. The 3D printed ultra-high performance concrete according to claim 2, characterized in that: In step (2), the mixture is stirred uniformly at a speed of 40 to 60 rpm for 8 to 12 minutes to obtain a modified limestone powder solution.

4. The 3D printed ultra-high performance concrete according to claim 1, characterized in that: The modified recycled brick aggregate is prepared by the following steps: (1) mixing the components of the recycled brick aggregate modifier to obtain a modifier solution; (2) adding the recycled brick aggregate to the modifier solution to obtain a modified recycled brick aggregate solution; (3) Seal the modified recycled brick aggregate solution and place it in a curing box for curing; (4) Separating the recycled brick aggregate from the solvent in the modified recycled brick aggregate solution and performing vacuum drying to obtain the modified recycled brick aggregate.

5. A method for preparing 3D printed ultra-high performance concrete according to claim 1, characterized in that: The following steps are involved: (1) Put cement, silica fume, modified limestone powder, modified recycled brick aggregate, coarse river sand and fine river sand into a mixer and mix to obtain a mixed dry material; (2) Mixing water and polycarboxylate water reducer to prepare a mixed solution, adding a portion of the mixed solution to the mixed dry material, stirring, and obtaining a mixture; (3) Pour the remaining part of the mixed solution into the mixture, add steel fiber during the stirring process, and stir evenly to obtain the mixture.

6. The method for preparing 3D printed ultra-high performance concrete according to claim 5, characterized in that: In step (2), the volume of the mixed solution used accounts for 85-95% of the total volume of the mixed solution.

7. The method for preparing 3D printed ultra-high performance concrete according to claim 5, characterized in that: In step (1), the mixture is stirred at a stirring speed of 40 to 60 rpm for 3 to 4 minutes to obtain a mixed dry material.

Citation Information

Patent Citations

  • Cement-based composite material for powder-bonding three-dimensional (3D) printing, and powder-bonding 3D printing method applying cement-based composite material

    CN106800391A

  • Dry-mixed masonry mortar prepared from recycled aggregate and preparation method thereof

    CN112608052A